The Factors associated with the practice of self-medication in Barumbu Health Zone, Democratic Republic of the Congo - Augustin KADIATA BUKASA; Augustin Tshitadi Makangu; Pascal Atuba Mamenepi; Marcel Tshidibi Bukasa; Sébastien Kazumba Mamba; Félicien Tshimungu Kandolo (Orapuh, Inc., 2024)
Introduction The issue of resorting to self-medication is currently common and no geographical area is spared from it in the world. Millions of people prefer to treat minor ailments rather than follow formal treatment. Purpose This study aimed to determine the factors associated with self-medication in the Barumbu Health Zone. Methods This is a descriptive correlational and cross-sectional study carried out in the city of Kinshasa, and more precisely in the Barumbu Health Zone. The sample was 266 heads of households. The questionnaire survey method was used with the structured interview technique to collect the data. Results After analysis with SPSS version 20 software, we arrived at the results according to which self-medication is practiced by 76.6%. Level of education (secondary) (X2 8.084, p=0.044) and monthly income ≤ 100$ (2 20.445., p=0.000) are associated with the practice of self-medication. Insufficient knowledge about the consequences of self-medication (X2 8.872, p= 0. 003), insufficient membership of mutual health insurance companies (X2 16,677, p=0.000), and the high cost of care (X2 30,304, p=0.000), are factors associated with the practice of self-medication in the commune of Barumbu, Kinshasa. Conclusion The revision of health care fees in all health care structures to allow everyone to access health care, the mobilisation to join mutual health insurance companies, and the sensitisation to the consequences of self-medication will allow to reduce this practice significantly.